Study of Literary Arts Education by Applying Basic Technique Learning Media of “Masatua” Bali - Gusti Ayu Erma Yunita Dewi; I Wayan Karja (Journal of Aesthetics, Creativity and Art Management, 2023)
The existence of application media can facilitate the learning system, because it can be used anytime and anywhere. All of this can affect the learning outcomes of students, especially in the field of Balinese past (telling satua Bali or Balinese fairy tales or stories). This paper aims to find out the study of interdisciplinary science contained in art and literature education (the Satua Bali) through the application of learning media on the basic techniques of the Balinese past. The method used in this study is a descriptive qualitative approach method. A qualitative approach is in the form of expressions, sentences and descriptions of form, aesthetics and meaning in satua Bali, as well as other scientific studies contained in satua Bali. Masatua Bali lessons are very important to be instilled in students, because indirectly they can learn various other scientific studies through satua Bali. The lack of utilization of instructional technology media is also one of the triggers for students' lack of interest in learning Balinese past which will certainly affect student outcomes.